Understanding gender disproportion and influences on subject choice in Physical Health Education: a British Columbia high school case study - St. Louis, April; Sharma, Manu (Sport, education and society, 2024)
The aim of this qualitative case study is to examine the phenomenon of female students' disproportionate representation in senior level Physical Health Education (PHE) classes. The subject for this teacher's Masters level project arose from the first author's personal observations while teaching across several schools in British Columbia, Canada. Through semi-structured interviews with self-identified female participants, we explore female subject choice and if, along with possible reasons why, females may avoid participation in senior level (grade 11-12) mixed gender PHE activity courses. This discussion asserts that females mostly make conscious choices to avoid mixed gender courses at the senior level for several key reasons; females feel silenced by their male peers, PHE is not an inclusive environment, and females perceive their male counterparts assert dominance over them in PHE class. This paper continues with a discussion regarding reinforced gendered norms and their effect on perceived barriers to female participation in schools, and concludes with suggestions for how schools and educators might support female students' participation.